Eastern Mediterranean hydroclimate reconstruction over the last 3600 years based on sedimentary n-alkanes, their carbon and hydrogen isotope composition and XRF data from the Gialova Lagoon, SW Greece. (15th August 2018) - Katrantsiotis, Christos; Kylander, Malin E.; Smittenberg, Rienk; Yamoah, Kweku K.A.; Hättestrand, Martina; Avramidis, Pavlos; Strandberg, Nichola A.; Norström, Elin
Abstract: Understanding past hydroclimate variability and related drivers is essential to improve climate forecasting capabilities especially in areas with high climatic sensitivity, such as the Mediterranean. This can be achieved by using a broad spectrum of high resolution, multiple proxy records which can also allow us to assess linkages between regional hydroclimate variability and shifts in the large-scale atmospheric patterns. Here, we present a multiproxy reconstruction of the central-eastern Mediterranean hydroclimate changes over the last 3600 years based on a sediment core from the Gialova Lagoon, a shallow coastal ecosystem in SW Peloponnese, Greece. Our combined dataset consists of the distribution and compound-specific carbon and hydrogen isotope (δ 13 C and δD) composition of n -alkanes, bulk organic matter properties and X-ray fluorescence (XRF) core scanning data. This approach was complemented with a semi-quantitative analysis of plant remains in the core. The results indicate a high contribution of local aquatic vegetation to organic matter. Large δ 13 C variations in predominantly aquatic plant-derived mid-chain alkanes (C23 - 25 ) mainly reflect changes in the aquatic plant abundance and their carbon source. Our data suggest that higher δ 13 C23-25 values (up to −19‰) largely correspond to expansion of aquatic vegetation during wet and/or cold periods causing carbon-limiting conditions in the water and assimilation of isotopically-enriched bicarbonate by the plants. The δD records of the individual n -alkanes (C17 to C31 ) exhibit a nearly identical pattern to each other, which implies that they all reflect changes in the source water isotope composition, driven by hydroclimate variability. In addition, the δD profiles are consistent with the XRF data with both proxies being driven by a common hydroclimate signal. We observe two major shifts from dry and/or warm periods at ca 3600-3000 cal BP and ca 1700-1300 cal BP to wet and/or cold episodes at ca 3000-2700 cal BP and ca 1300-900 cal BP. The period ca 700-200 cal BP is the wettest and/or coldest in our record and coeval with the Little Ice Age. The climatic fluctuation reported in this study can be explained by the relative dominance of high-latitude (e.g. North Atlantic Oscillation during winters) and the low-latitude atmospheric patterns (Intertropical convergence zone, Subtropical High and the effects of Asian monsoons during summers) which suggests an Atlantic-Mediterranean-Monsoon climate link in this area for the late Holocene. Highlights: We measured δ 13 C and δD of n -alkanes combined with XRF data from a sediment core taken at the Gialova Lagoon, SW Greece. The δD of the individual n -alkanes generally co-varies with the XRF data reflecting common hydroclimate-driven changes. The Gialova record displays three major shifts from dry/warm to wet/cold periods during the last 3600 years. The climatic fluctuation can be explained by the relative dominance of high-latitude and low-latitude atmospheric patterns. Dry conditions in the Gialova record are associated with enhanced monsoon periods in East Africa and Asia.